Functional outcome of TENS nailing for paediatric long bone fractures - Sujaya, Amal Prabhakaran; Reddy, R. M. Mallikarjuna; Nadarajan, Ebel Raj; Teja, Ande Sai (International Journal of Research in Orthopaedics, 2025)
Musculoskeletal trauma constitutes a major portion of paediatric injuries. Titanium elastic nailing system (TENS) has emerged as a minimally invasive and effective method for internal fixation of long bone fractures in children.This study evaluates the functional outcome of TENS nailing in paediatric long bone fractures and compares the results with established literature. A prospective study of 20 children (aged 2–12 years) with diaphyseal fractures of femur, tibia, humerus, and forearm bones treated with TENS was conducted at ASRAM Medical College, Eluru, during 2023–2024. Patients were followed up clinically and radiologically at 1, 3, and 6 months postoperatively. Implant removal was planned at one year. The study included 14 males and 6 females. The most common cause of injury was accidental fall (65%), followed by road traffic accidents (25%). Excellent results were seen in 90% of cases and satisfactory in 10% of cases. The average hospital stay was 10 days, average blood loss was 45 ml, and the mean time to union was 4 months. Complications included knee stiffness (5%) and superficial infection (10%), which resolved with physiotherapy and antibiotics, respectively.